2023
DOI: 10.3390/metabo13040496
|View full text |Cite
|
Sign up to set email alerts
|

Expression of STING in Women with Morbid Obesity and Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic hepatic disease. Although mostly benign, this disease can evolve into nonalcoholic steatohepatitis (NASH). The stimulator of interferon genes (STING) plays an important role in the immune response against stressed cells, but this protein may also be involved in liver lipogenesis and microbiota composition. In this study, the role of STING in NAFLD was evaluated by RT–qPCR to analyze STING mRNA abundance and by immunohistochemical analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Fibrosis is a critical characteristic of advanced NAFLD, and its presence may influence STING expression differently compared to earlier stages of the disease. 30 Studies have also found that the levels of cGAS and STING proteins increased in liver carcinoma patients with the increase in liver fibrosis, and were higher than in the surrounding cancer tissues. 31 These contrasting findings highlight the complexity of the STING signaling pathway’s involvement in NAFLD and the need for further research to fully understand its role in different stages of the disease.…”
Section: Sting Signaling Pathway In Nafldmentioning
confidence: 97%
“…Fibrosis is a critical characteristic of advanced NAFLD, and its presence may influence STING expression differently compared to earlier stages of the disease. 30 Studies have also found that the levels of cGAS and STING proteins increased in liver carcinoma patients with the increase in liver fibrosis, and were higher than in the surrounding cancer tissues. 31 These contrasting findings highlight the complexity of the STING signaling pathway’s involvement in NAFLD and the need for further research to fully understand its role in different stages of the disease.…”
Section: Sting Signaling Pathway In Nafldmentioning
confidence: 97%